Inclusión de harina de cúrcuma (Curcuma longa) en la ración de pollos parrilleros, etapa acabado y su efecto sobre la pigmentación y parámetros productivos - Rojas García, Melissa (2024)
The present research was developed in the district of Yurimaguas, whose purpose was to evaluate the inclusion of turmeric flour (HC) in the ration of broiler chickens, finishing stage and its effect on pigmentation and productive parameters of the skin. The productive parameters evaluated were: feed consumption, weight gain, feed conversion, mortality, carcass yield. 120 male Cobb 500 chickens, 21 days old, were used. The statistical design used was Completely Randomized with three treatments and four repetitions. The treatments were, T0 (control treatment); T1: 1% HC; T2: 2% HC. The results indicate that for skin pigmentation, chickens from T2 showed the highest coloration with ranges between 6 and 7, followed by T1, with a range between 3 and 4. Regarding total feed consumption, they have for T0: 4,685.29 g , T1: 4,768.66 g and T2: 4,799.14 g, while, for the accumulated weight gain, 2,817 g were obtained in T0, T1: 2,905 g and T2: 2,814 g. T0: 1,663, T1:1,642 and T2:1,705. Statistically, there were no significant differences (p>0.05) between the study treatments. In the casing performance, the T2 achieved the best percentage with 70.51%. No mortality was recorded. It is concluded that T2 (2% HC) achieved the best degree of pigmentation, while T1 (1% HC) obtained the best results regarding the productive parameters.